PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA YAYASAN NURUL FALAH SURADITA KABUPATEN TANGERANG - Heli Suhaeli; Iskandar Zulkarnain (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. The purpose of this research is to determine the effect of leadership and the physical work environment on employee performance at Yayasan Nurul Falah Suradita, Tangerang Regency. This study uses a quantitative approach with a saturated sampling technique involving 54 respondents. Data analysis methods include validity testing, reliability testing, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results show that leadership has a significant effect on employee performance, indicated by the linear regression equation Y = 19.640 + 0.534X1, with a correlation coefficient of 0.524 and a coefficient of determination of 27.5%. Hypothesis testing also shows that t-count is greater than t-table (4.438 > 1.675). The physical work environment also has a significant effect on employee performance, with the regression equation Y = 16.959 + 0.594X2, a correlation coefficient of 0.568, and a coefficient of determination of 32.3%, where t-count is greater than t-table (4.981 > 1.675). Simultaneously, leadership and the physical work environment significantly influence employee performance, with a correlation coefficient of 0.680 and the regression equation Y = 6.827 + 0.398X1 + 0.474X2. The coefficient of determination is 46.3%, while the remaining 53.7% is influenced by other factors not examined in this study. Keywords: Leadership, Physical Work Environment, Employee Performance